Localized microstructural characterization of a dissimilar metal electron beam weld joint from an aerospace component. (15th January 2016) - Jothi, Sathiskumar; Sebald, Torsten; Davies, H.M.; Reese, Eggert D.; Brown, S.G.R.
Abstract: Hydrogen induced cold cracking (HICC) and hydrogen embrittlement (HE) are influenced by the microstructural evolution, residual plastic strain (i.e. local misorientation), recrystallization of grains and the resultant grain boundary characteristic distribution (GBCD) brought about by welding processes. HICC and HE are known to cause failures in aerospace components and it is vitally important to quantify the microstructural evolution, degree of residual plastic strain and determine the GBCD across dissimilar weld joints in order to assess the susceptibility of the weld joint to these phenomena. In this investigation a full a microstructural characterization study was carried out at various locations within and around a dissimilar weld joint of pulse-plated nickel (PP-Ni) and Inconel 718 (IN718), taken from an aerospace component. Areas examined included the base metals, weld fusion zone and heat affected zones on both sides of the weld joint, formed via electron beam welding. Scanning electron microscopy (SEM) in combination with electron backscatter diffraction (EBSD) was employed to measure the residual plastic strain, grain structure, grain size distribution, crystal orientation distribution, grain boundary misorientation distribution and GBCD of the dissimilar metal weld joint. Finally a metallurgical examination was carried out using SEM on the IN718 HAZ in order to investigate the secondary phase precipitation arising from the welding process. The results shows large variety of GBCD, crystallographic orientation distribution, local plastic strain distribution and grain size, shape and structure distribution across dissimilar weld joint. And these localized microstructural characterized data sets need to be carefully transferred using data-driven approach in order to develop predictive multiscale material modelling for hydrogen induced cracking and hydrogen embrittlement. Graphical abstract: Highlights: Microstructure evolution in dissimilar weld joint was investigated. Areas examined included the base metals, weld fusion zone and HAZs of weld joint. SEM/EBSD was employed to measure the residual plastic strain, crystal orientation. Grain boundary characteristic and grain structure distributions are also examined. The influence of microstructural features on hydrogen diffusion has been discussed.